Morphological variation and its taxonomic implications for insular populations of Pseudocrenilabrus philander (Pisces: Cichlidae) - Twentyman Jones, Vanessa (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1993)
The cichlid fish Pseudocrenilabrus philander is widely distributed in southern Africa. Many of the populations occur in small, insular, geographically isolated water bodies, some of which are in arid areas. These small allopatric populations have been isolated for thousands of years and gene flow between them is non-existent or severely restricted. Populations were found to be different in terms of coloration, size of individuals, sexual dimorphism and behaviour. This thesis involved the determination of the taxonomic status of these isolated populations, from a morphological point of view. This has been part of a larger project, involving genetic and behavioural studies, to determine whether the different populations are geographic races of a single species, or whether they are species. Heritability of the observed differences was tested by breeding through three generations under uniform laboratory conditions. The populations from which wild-caught individuals were drawn could be identified on the basis of colour. There were some differences in anatomy between populations, but none of these were entirely distinctive for a particular population. When bred under laboratory conditions, populations did not show a tendency towards uniformity, as would be expected if morphological differences were environmentally induced. However, there were slight changes in the oral and pharyngeal bone form which may be diet related. Although there are morphological differences between populations and between wild-caught and laboratory-bred populations, it is suggested that the populations of P. philander are not fully differentiated and thus in the stages of incipient speciation. other studies on P. philander have introduced an element of uncertainty in that they show different results. Behavioural work suggests that different populations would behave as different species if they were to become sympatric. Karyological and mitochondrial studies showed that there were no differences between populations. Protein electrophoresis showed that populations were genetically unique. Since the various species and subspecies of Pseudocrenilabrus have been based on morphological criteria, the approach and conclusions in this study are based entirely on morphological criteria. These studies have practical implications for conservation, as some of the small populations are threatened with extinction. If the differences between the populations were ecophenotypic (i.e. related to their environment), then threats to some populations would not affect the conservation status of the species as a whole. If, however, such differences were genetic (i.e. the populations have evolved separately), then the extinction of small, isolated populations could mean the loss of actual species. This study strongly suggests that populations are incipient species and thus should be conserved.
Keywords: Cichlids -- Morphology; Cichlids -- Conservation; Freshwater fishes -- Conservation -- Africa, Southern